THE ABILITY OF THE SECOND YEAR STUDENTS OF SMK NEGERI NIBAAF IN WRITING NARRATIVE TEXT - Florida Tay Kabosu; Imanuel Kamlasi (Kopertis Region IV Jabar and Banten, 2020)
Abstract:In this research discussed about how the students the ability writing narrative text of the personal narrative tex in the story. This study aims to answer the problems: have the students mastered to write narrative text. What aspect writing of narrative text is still difficult for them to master to write. To what level is their ability on writing narrative text categorized. In this study, the writer use descriptive qualitative method and the way to get the data, the writer use the writing test. The populations of this study is the second grand students of SMK Negeri Nibaaf in the school year 2019/2020 consisting of class XII TRRH 21 students, but only 10 students were choosen as sample of this study. The result of finding show that the second ability in composing narrative writing with the instrument given is categorized good. It is SMK Negeri Nibaaf have abilities in composing a good narrative writing. It can be seen from the averange score of content is 4,1 vocabulary is 3,6 and language use is 3,8. After analized the data and got the result, the are some conclusion are all the students have mastered narrative writing. on the basic of the averange score good, vocabulary is difficult part of aspect of narrative writing. the students level of mastery is categorized good. It is based on the data that there are 4 of 10 on this level of mastery. Therefore, the second students of SMK Negeri Nibaaf have mastered in writing.Keywords: Ability, writing, narrative.